Der Kalte Krieg und die Asienkrise - Johnson, Chalmers (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
The Cold War relationships in Asia are an important reason for the present crisis. They caused serious overcapacities throughout the Asian region. Moreover, by devaluating their currency China and Japan had strongly improved their competitiveness against the »Asian Tigers«. When foreign capital was pulled out of these economies, it came to liquidity crunch. For overcoming the crisis not only financial measures but new relationships in the Pacific region are necessary.